Standardized 3D Bioprinting of Soft Tissue Models with Human Primary Cells. (August 2016) - Rimann, Markus; Bono, Epifania; Annaheim, Helene; Bleisch, Matthias; Graf-Hausner, Ursula
Cells grown in 3D are more physiologically relevant than cells cultured in 2D. To use 3D models in substance testing and regenerative medicine, reproducibility and standardization are important. Bioprinting offers not only automated standardizable processes but also the production of complex tissue-like structures in an additive manner. We developed an all-in-one bioprinting solution to produce soft tissue models. The holistic approach included (1) a bioprinter in a sterile environment, (2) a light-induced bioink polymerization unit, (3) a user-friendly software, (4) the capability to print in standard labware for high-throughput screening, (5) cell-compatible inkjet-based printheads, (6) a cell-compatible ready-to-use BioInk, and (7) standard operating procedures. In a proof-of-concept study, skin as a reference soft tissue model was printed. To produce dermal equivalents, primary human dermal fibroblasts were printed in alternating layers with BioInk and cultured for up to 7 weeks. During long-term cultures, the models were remodeled and fully populated with viable and spreaded fibroblasts. Primary human dermal keratinocytes were seeded on top of dermal equivalents, and epidermis-like structures were formed as verified with hematoxylin and eosin staining and immunostaining. However, a fully stratified epidermis was not achieved. Nevertheless, this is one of the first reports of an integrative bioprinting strategy for industrial routine application.